Protocol for modeling blood flow recovery and angiogenesis in response to hindlimb ischemia - Sheila Sharma; Julia Pierce; Celia A. Butler; Olivya Caballero; Chris Mantsounga; Alan R. Morrison (STAR Protocols)
Summary: Here, we present a protocol that models peripheral artery disease using the surgical induction of hindlimb ischemia (HLI) in mice. We list the steps to surgically excise the femoral artery and assess blood flow recovery through laser Doppler imaging. We then detail procedures for visualizing immune cell recruitment and blood vessel growth to explore the role of inflammatory macrophages in angio/arteriogenesis.For complete details on the use and execution of this protocol, please refer to Mantsounga et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.